The Effect of Social Commerce Platforms and Perceived Product Quality on Product Sales Growth, Moderated by Digital Promotional Strategies: A Case Study at Zahra Store in Tebo Regency, Jambi Province - Chairunnisa Azzahra; Vivi Yosefri Yanti; Rita Zunarti (International Journal of Management Science and Information Technology, 2026)
This study aims to analyze the influence of social commerce platforms and product quality perception on the increase in cosmetics sales, with digital promotion strategies serving as a moderating variable among Zahra Store customers in Tebo Regency, Jambi Province. Amidst intense competition in the cosmetics industry, local MSMEs face challenges in market reach, making the integration of social commerce and product excellence critical to explore. Employing a quantitative approach with an explanatory research design, data were collected from February to May 2026 via questionnaires based on a 5-point Likert scale administered to 150 purposively sampled respondents. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) via SmartPLS 4. The structural model evaluation shows an R-square value of 0.586, indicating that platform social commerce and product quality perception simultaneously explain 58.6% of the variance in sales growth. Individually, product quality perception (β = 0.566, t = 12.813, p = 0.000) and platform social commerce (β = 0.458, t = 9.271, p = 0.000) exert positive and significant direct effects on product sales increase. Conversely, digital promotion strategy shows neither a significant direct effect (β = 0.119, p = 0.096) nor a significant moderating role in the model (p > 0.05). These findings imply that regional retail sales are primarily driven by direct platform utility and core product quality, rather than external promotional gimmicks. Practically, local MSMEs in non-urban sectors should focus their limited resources on maintaining high product reliability and optimizing native interactive features such as direct chat responsiveness and seamless catalog access instead of investing heavily in high-cost digital advertisement campaigns.